Plasma electric potential evolution at the core and edge of the TJ-II stellarator and T-10 tokamak - Krupnik, L.; Zhezhera, A.; Melnikov, A.; Hidalgo, C.; Alonso, A.; Chmyga, A.; Eliseev, L.; Komarov, A.; Kozachok, A.; Lysenko, S.; de Pablos, J.L.; Perfilov, S. (Вопросы атомной науки и техники, 2006)
In this article are presented main results on electric potential investigations in stellarator/torsatron TJ-II and tokamak T-10 in a comparable regimes of device operation. Представлены основные результаты исследований электрического потенциала плазмы, полученного на стеллараторе/торсатроне TJ-II и токамаке Т-10 при идентичных режимах работы установок. Представлено основні результати досліджень електричного потенціалу плазми, одержаного на стелараторі/торсатроні TJ-II та на токамаці Т-10 при ідентичних режимах роботи пристроїв